Development of Interactive E-Modules for Differentiated Learning to Improve Critical Thinking Skills and Student Learning Outcomes on Body Defense System Materials - Zahra, Khustiana; Purwantoyo, Eling (Universitas Negeri Semarang, 2024)
The results of the PISA study in 2015 show that the critical thinking ability of the majority of students in Indonesia is still low. The low critical thinking ability of students is an indicator that determines the quality of student learning outcomes. One of the reasons is that there are not many learning media that are able to facilitate the diversity of student learning that can be accessed by mobile. E-Modules that are made specifically for differentiated learning are media developed to answer these problems. The purpose of this study is to determine the characteristics, feasibility, and effectiveness of interactive e-modules in differentiated learning to improve students' critical thinking skills and learning outcomes. This study refers to the development research design of Borg and Gall which consists of 10 steps, but the researcher only conducts research up to the eighth step, namely Operational Field Testing. Data collection was carried out by interview, questionnaire and test methods (pretest and posttest). The data analysis techniques in this study are descriptive analysis, feasibility percentage analysis and N-Gain test. The e-module developed has a special characteristic, namely the existence of features that support differentiating content, processes and products based on visual and auditory learning styles. The results of the e-module feasibility test by validators of media experts and material experts, both received very feasible criteria with percentages of 99.3% and 93.4%. In the feasibility test by users, very feasible criteria were also obtained, both in the teacher's response and the student's response, with a percentage of 96% and 83.25%, respectively. In the N-Gain test, the results of the e-module were also found to be effective in improving students' critical thinking skills and learning outcomes, with an average class N-Gain score of 0.85. So the conclusion is that the interactive e-module on differentiated learning has proven to be feasible and effective in improving students' critical thinking skills and learning outcomes on the Body Defense System material.